2008
DOI: 10.1002/ajmg.a.32505
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibilities in the association between maternal exposure to tobacco smoke and the risk of nonsyndromic oral cleft

Abstract: Maternal tobacco consumption is considered as a risk factor for nonsyndromic oral clefts. However, this risk is moderate and may be modulated by genetic susceptibilities, including variants of the TGFA, TGFB3 and MSX1 developmental genes and polymorphisms of genes of the CYP (1A1, 2E1) and GST (M1, T1) families involved in metabolic pathways of tobacco smoke compounds. This French case-control study (1998-2001; 240 nonsyndromic cases, 236 controls) included a case-parent design (175 triad-families) that made i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
(65 reference statements)
1
38
0
7
Order By: Relevance
“…6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups. The presence of partial palatal seam in the newborn pups, which otherwise would have disintegrated at 14.5 to 16.5 dpc indicates: (1) the growth of the palate towards each other to form a seam, although in smaller size and shape, is not altered; (2) the genes that causes immaculate seam disintegration might have been effected by nicotine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups. The presence of partial palatal seam in the newborn pups, which otherwise would have disintegrated at 14.5 to 16.5 dpc indicates: (1) the growth of the palate towards each other to form a seam, although in smaller size and shape, is not altered; (2) the genes that causes immaculate seam disintegration might have been effected by nicotine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, в ряде исследований изучалось влия-ние полиморфизма генов, вовлеченных в регулирование продукции связанных с табакокурением АФК. Аллельные варианты фетального гена CYP1A1, участвующего в акти-вации химических веществ табачного дыма, уменьша-ли риск возникновения оральных расщелин [50,51]. Вместе с тем для детоксицирующего фермента глутатион-S-трансферазы показано, что делеции в гене GSTT1 свя-заны с высоким риском развития оральных расщелин у детей, чьи матери курили [51,52].…”
Section: окислительный стрессunclassified
“…Вместе с тем для детоксицирующего фермента глутатион-S-трансферазы показано, что делеции в гене GSTT1 свя-заны с высоким риском развития оральных расщелин у детей, чьи матери курили [51,52]. Однако, этот риск не наблюдался в случае делеций в гене GSTM1 [50,53]. Вари антные аллели в генах N-ацетилтрансферазы 2…”
Section: окислительный стрессunclassified
“…The most common risk factors reported were maternal exposure to tobacco products [81,82], alcohols [83], some viral infections [70], pesticides [84], and teratogens in the workplace or at home in early pregnancy [85][86][87]. Recognized teratogens included rare exposures such as phenytoin, valproic acid, thalidomide, and herbicides such as dioxin.…”
Section: Maternal Exogenous Exposuresmentioning
confidence: 99%